Serum Calcium Level in Patients with Pre Eclampsia : A Case Control Study (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: To compare serum calcium level in pre-eclamptic women and normal pregnant women.Materials and methods: It was a case-control study carried out in patient Department of Fetomaternal Medicine unit in the Department of Obstetrics & Gynaecology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. From September 2010 to February 2011. Total 60 cases, among them 30 comprising control group and 30 were cases. This was a non interventional case control study that was carried out on total 60 women with age range 18 to 38 years of them 30 healthy gravid women as control group and 30 pregnancy with pre eclampsia as case. Serum calcium level of the groups were measured, and compare between this two group. Data were analyzed by computer with the help of SPSS (Statistical Package for Social Sciences) win 13 software package.Results: Serum calcium in pre-eclamptic women was significantly low [7.88±0.75mg/dl vs 9.9267±0.58 mg/dl] than in normal pregnant women.Conclusion: Serum calcium may be used for earlier detection of preeclampsia. Further studies are required to investigate whether calcium supplementation can be used as a preventable measure for the development of preeclampsia.Chatt Maa Shi Hosp Med Coll J; Vol.20 (1); January 2021; Page 33-36